Pathways to deeper roots: anatomical phenes of maize under impedance - Vanhees, Dorien J. (2020)
When roots grow through soil they experience mechanical impedance to varying extents. When levels of mechanical impedance become greater, for instance when soils become compacted or soil moisture decreases, roots can become obstructed. As a consequence the uptake of nutrients and water from the soil reduces, which can reduce plant growth and ultimately negatively impact yield. In this work field trials were conducted at two different field sites (one at the Apache Root Biology Centre in Willcox, Arizona and one at the Russell E. Larson Agricultural Research Center in Rock Springs, Pennsylvania) to study the differential distribution of maize roots following the interaction with a compacted soil profile. In soils with compacted plots the rooting depth of coarse roots was not correlated with coarse root length, which indicated that nodal roots of some genotypes were able to grow under impeding conditions while other genotypes were not capable of growing through impeding conditions. Furthermore genotypes were identified which had similar rooting depths but contrasting coarse root lengths, these genotypes were equally able to reach to deeper depths. The amount of roots formed by the root system therefore does not determine the ability of roots to grow deeper under impeded conditions. Root thickening, a response of roots often seen when submitted to mechanical impedance, varied among genotypes. The same field trial were also used to investigate the role of root anatomy and adaptation to soil mechanical impedance. Root anatomy varied according to genotype and nodal position. Deeper rooting was facilitated by root anatomical phenes such as reduced cortical cell file number in combination with greater middle cortical cell area for node 3 and increased aerenchyma for node 4.